Self-esteem and peer relations : a comparison between adolescents with cerebral palsy in a special school and able-bodied adolescents in a mainstream school - Jessica Letchamanan (2008)
A healthy sense of self-esteem and good peer relations are among the few elements that are important for one to reach his/her full potential. While a number of theorists have suggested that individuals with disabilities have a lower sense of self-worth compared to their able-bodied counterparts, some other empirical findings have found no significant difference between the self-esteem of both groups. In the light of this, and the lack of such studies in Singapore, this study aims to ascertain the self-esteem and peer relations of adolescents with cerebral palsy (CP) in Singapore by comparing this with their able-bodied counterparts in a mainstream secondary school. The Self-Esteem Checklist (SEC) and the Index of Peer Relations (IPR) were administered to adolescents with CP in a special school and able-bodied adolescents in a mainstream secondary school and the responses of 30 from each group were selected for data analysis based on background information that matched. This information include the variables of age, family structure, parents' educational level and family's social-economic status. The mean scores on the SEC and IPR of both groups were compared using a one-way analysis of variance. The findings indicate that adolescents with CP had a significantly higher self-esteem (p < 0.025) than their able-bodied counterparts, and that there were no significant differences between the peer relations of both groups.